Komodifikasi Pariwisata Halal NTB dalam Promosi Destinasi Wisata Islami di Indonesia - Awalia, Hafizah (Jurnal Studi Komunikasi, 2017)
Halal tourism destination becomes the new brand for West Nusa Tenggara. Strong local ethnic and religious plurality obtain halal tourism label. It is important to assess if the government saw the domination of the discourse object of power through the economic and tourism sectors. Therefore, this discourse halal tourism can be evaluated using the perspective of post-modern social theory Michael Foucault discourse and power: the power elite that is capable of creating a new discourse (halal tourism) to strengthen its political dominance. Then, using the perspective of Baudrillard's theory of the emergence of consumerist society in NTB as a result of capital commodification and domination of the capitalists.Â Keywords: Commodification, Discourse, Tourism, HalalÂ